Wpływ nauki na etykę życia gospodarczego na podstawie sporu o ceny drapieżne - Trojanowska, Hanna (Annales. Etyka w Życiu Gospodarczym, 2012)
Chicago School argues that the use of predatory strategy may not lead to a profit. Postchicago School, investigating this problem onthe basis of game theory, argues just the opposite. This dispute on the basis of theoretical economics, has an impact on ethics in economiclife. In a number of lawsuits companies rely on the views of the Chicago School to win, which raises the ethical concerns.